Towards Sustainable Electricity Generation: A Review of Renewable and Non-Renewable Energy Sources - Ekundayo Gbenga; Oluwalami Abimbola Samuel (Current Approaches in Engineering Research and Technology Vol. 6, 2024)
As the global population grows and socio-economic development advances, the need for electricity continues to increase. However, the widespread use of fossil fuels for electricity generation has been reviewed to contribute 75% of the environmental pollution and presents a significant threat to the environment due to carbon dioxide emissions, exacerbating global warming. This paper explores various methods of electricity generation, encompassing non-renewable and renewable sources. It underscores the pressing need for increased research and investment in technologies to enhance the operational efficiency of renewable energy sources. By prioritising renewable energy development, especially in regions like Nigeria, where the full impact of global warming is not yet felt, we can achieve sustainable electricity generation, ensuring a cleaner and more secure energy future.